Comprehensive analyses of microRNA gene evolution in paleopolyploid soybean genome. (23rd August 2013) - Zhou, Zhengkui; Wang, Zheng; Li, Weiyu; Fang, Chao; Shen, Yanting; Li, Congcong; Wu, Yunshuai; Tian, Zhixi
Summary miRNA genes are thought to undergo quick birth and death processes in genomes and the emergence of a MIRNA‐like hairpin provides the base for functional miRNA gene formation. However, the factors affecting the formation of an active miRNA gene from a MIRNA‐like hairpin within a genome remain unclear. We performed a genome‐wide investigation of MIRNA‐like hairpin accumulation, expression, structural changes and relationships with annotated genomic features in the paleopolyploid soybean genome. Our results showed that adjacent gene and transposable element content, rates of genetic recombination at location of emergence, along with its own gene structure divergence greatly affected miRNA gene evolution. Further investigation suggested that miRNA genes from different duplication sources followed distinct evolutionary trajectories and that the accumulation of MIRNA‐like hairpins might be an important factor in causing long terminal repeat retrotransposons to lose activity during genome evolution.